2016
DOI: 10.1016/j.jalz.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

CNS tau efflux via exosomes is likely increased in Parkinson's disease but not in Alzheimer's disease

Abstract: Background Alzheimer disease (AD) and Parkinson disease (PD) involve tau pathology. Tau is detectable in blood, but its clearance from neuronal cells and the brain is poorly understood. Methods Tau efflux from the brain to the blood was evaluated by administering radioactively labeled and unlabeled tau intracerebroventricularly in wild-type and tau knock-out mice, respectively. Central nervous system (CNS)-derived tau in L1CAM-containing exosomes was further characterized extensively in human plasma, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
167
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 171 publications
(180 citation statements)
references
References 28 publications
4
167
0
Order By: Relevance
“…However, recent studies have reported increased P‐tau concentrations in neuron‐derived exosomes isolated from serum using antibodies directed against neuron‐enriched proteins (Shi et al . ; Winston et al . ).…”
Section: Biomarkers For Tau Pathologymentioning
confidence: 99%
“…However, recent studies have reported increased P‐tau concentrations in neuron‐derived exosomes isolated from serum using antibodies directed against neuron‐enriched proteins (Shi et al . ; Winston et al . ).…”
Section: Biomarkers For Tau Pathologymentioning
confidence: 99%
“…; Shi et al . ). One recent development, reported by two independent studies, is the significantly different Aβ 42 /Aβ 40 ratio among amyloid positive versus negative patients which may provide improved diagnosis for patients with ambiguous CSF Aβ 42 or tau results, and may have sparked some hope back into blood‐derived biomarked development for AD (Ovod et al .…”
Section: Biomarkers For Ad and Pdmentioning
confidence: 97%
“…Furthermore, we have recently used immunoassay detection platforms to report that CNS‐derived EVs within plasma of the contain altered levels of α‐syn and tau in PD (Shi et al . ; Shi et al ., ). These studies hint at the potential utility of plasma EVs as a future biomarker resource that maintains the clinical ease of blood collection but avoids many of the complications involved with blood alone.…”
Section: Biomarkers For Ad and Pdmentioning
confidence: 97%
See 1 more Smart Citation
“…As such, the results may not necessarily reflect contents of a bona fide exosome population but include other lipid vesicles as well. In contrast, an independent group recently reported that tau was not found to be associated at higher levels with neural-derived EVs isolated from plasma of AD patients [90]. Using isolation of neural-derived EVs from human plasma, it was also found that the abundance of several proteins was altered up to 10 years prior to AD diagnosis [91].…”
Section: Exosomes As Biomarker Vehicles For Admentioning
confidence: 99%